2010
DOI: 10.1590/s1676-26492010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the employment situation and driving license of patients with epilepsy

Abstract: INTRODUCTION: It is estimated that approximately 50% of patients with epilepsy have difficulty finding employment. OBJECTIVE: Evaluate the employment situation and driving license of patients with symptomatic or probably symptomatic focal epilepsy and correlate it with clinical and socio-demographic aspects. METHODS: Ninety-two patients were classified into 3 groups: "employed", "unemployed" and "retired/on leave". The relationship between employment and socio-demographic aspects and those of epilepsy was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…The majority of patients (76.7%) evaluated for a driving license after the diagnosis of epilepsy omitted this diagnosis to get their license. These numbers were similar to that found in another Brazilian study from Campinas [17] and well above those found in the study of Elliott and Long [18], where only 19% said that they had omitted this information [18].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of patients (76.7%) evaluated for a driving license after the diagnosis of epilepsy omitted this diagnosis to get their license. These numbers were similar to that found in another Brazilian study from Campinas [17] and well above those found in the study of Elliott and Long [18], where only 19% said that they had omitted this information [18].…”
Section: Discussionsupporting
confidence: 90%
“…Outros estudos revelam maiores taxas de desemprego entre epiléticos que na população geral e associam este achado a aspectos do agravo e de ordem social, tais como ocorrência de crise epilética no ambiente de trabalho e baixo nível de escolaridade 19 Considerando a magnitude da epilepsia no mundo e em países em desenvolvimento como o Brasil, suas profundas repercussões negativas sobre a qualidade de vida e capacidade laborativa dos indivíduos, a elevada frequência com que sujeitos com epilepsia se apresentam aos serviços de perícia médica pleiteando a constatação de incapacidade laborativa e as dificuldades vivenciadas pelo médico perito no momento de emitir sua decisão, justifica-se a realização do presente estudo, de modo a revisar e organizar achados de literatura sob a forma de material de apoio à tomada de decisão médico-pericial.…”
Section: Introductionunclassified